Comparative Perspectives in Economic Crises Geography. Economic Strategies in EU Countries - Roxana Maria Grecu (CES Working Papers, 2011)
The strategies for structural-systemic crisis management have generated, to a geographical level, a number of differences between EU countries. These cleavages are the result of differential macroeconomic policies. In this context, this article has the aim of achieving a comparative approach between countries of the south, west and east of the EU space. Also our approach is focused on observing the nature of macroeconomic policies and also on identifying a "pattern" associated with a common ideal -type of "rational choice" in the efficient and effective management of systemic crises. This article aims to identify areas of growth and economic stability of a particular model of public policy and political-economic ideology, to set up a mechanism for "economic engineering”. From the methodological point of view, this article uses a quantitative methodology, derived from mathematical analysis, statistics and stochastic, in order to explain, understand and predict the possible evolution of the systemic crises in the EU countries. The interest lies in the possibility of giving a model of macroeconomic policy for the adjustment of inflationist imbalances, labor market and price policy, and also in regulating the equation of production-consumption.
Keywords: 330; economic crises; EU free market; economic cycle; GDP evolution; economic geography; comparative approach Romania